2018
DOI: 10.1111/1742-6723.13131
|View full text |Cite
|
Sign up to set email alerts
|

Review article: Best practice management of neck pain in the emergency department (part 6 of the musculoskeletal injuries rapid review series)

Abstract: Neck pain and whiplash injuries are a common presentation to the ED, and a frequent cause of disability globally. This rapid review investigated best practice for the assessment and management of musculoskeletal neck pain in the ED. PubMed, CINAHL, EMBASE, TRIP and the grey literature, including relevant organisational websites, were searched in 2017. Primary studies, systematic reviews and guidelines were considered for inclusion. English-language articles published in the past 12 years addressing acute neck … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…In purest terms, imaging findings (when warranted per standard guidelines) in tandem with other known risk factors may increase confidence of the primary, secondary, tertiary drivers of an individual patient's recovery trajectory, which should ultimately inform a plan of care. It is noteworthy that 61% (59/97) of those acutely injured (and enrolled in our parent study), were not referred for imaging, which befits best practice management of traumatic neck pain and suggests judicious use of clinically indicated imaging through available guidelines and clinical experience [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In purest terms, imaging findings (when warranted per standard guidelines) in tandem with other known risk factors may increase confidence of the primary, secondary, tertiary drivers of an individual patient's recovery trajectory, which should ultimately inform a plan of care. It is noteworthy that 61% (59/97) of those acutely injured (and enrolled in our parent study), were not referred for imaging, which befits best practice management of traumatic neck pain and suggests judicious use of clinically indicated imaging through available guidelines and clinical experience [12].…”
Section: Discussionmentioning
confidence: 99%
“…The American College of Radiology Appropriateness Criteria (ACR-AC) is the principal guideline in the United States for clinical decisions regarding the use of diagnostic imaging. Similar societal guidelines supported by the same body of evidence and informed by the criteria set forth in the Canadian Cervical Spine Rule and/or the National Emergency X-Radiography Utilization Study (NEXUS) [11] are available worldwide [12].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, while MRI measures of MFI have shown to be related to the severity of whiplash, referral for MR imaging in the acute stage is not considered to be 'usually appropriate' per available guidelines of suspected spine trauma unless there is neurological involvement or overt ligamentous injury is suspected. [47][48][49] In the absence of overt cervical trauma or neurological deficits, CT is the preferred initial imaging modality given the primary concern for fracture. CT can also be used to evaluate the composition of muscle, but whether or not standard-of-care CT measures of muscle fat (determined by lower radiation attenuation) are also related to MRI findings of neck MFI and the clinical course of whiplash is currently unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that different clinical practice guidelines for diabetes-related osteomyelitis may result in conflicting recommendations, reducing the effectiveness of treatment [ 65 , 66 ]. However, there is no generally agreed-upon treatment protocol for diabetes associated with osteomyelitis, making its management more difficult than in other diabetes-related conditions [ 67 ].…”
Section: Discussionmentioning
confidence: 99%